Effects of low-level combined static and weak low-frequency alternating magnetic fields on cytokine production and tumor development in mice. (2nd January 2019) - Novoselova, Elena G.; Novikov, Vadim V.; Lunin, Sergey M.; Glushkova, Olga V.; Novoselova, Tatyana V.; Parfenyuk, Svetlana B.; Novoselov, Sergey V.; Khrenov, Maxim O.; Fesenko, Evgeny E.
ABSTRACT: We investigated the effects of weak combined magnetic fields (MFs) produced by superimposing a constant MF (in the range 30 - 150 µT) and an alternating MF (100 or 200 nT) on cytokine production in healthy Balb/C male mice exposed 2 h daily for 14 days. The alternating magnetic field was a sum of several frequencies (ranging from 2.5 - 17.5 Hz). The frequencies of the alternating magnetic field were calculated formally based on the cyclotron resonance of ions of free amino acids (glutamic and aspartic acids, arginine, lysine, histidine, and tyrosine). The selection of different intensity and frequency combinations of constant and alternating magnetic fields was performed to find the optimal characteristics for cytokine production stimulation in immune cells. MF with a constant component of 60 μT and an alternating component of 100 nT, which was a sum of six frequencies (from 5 to 7 Hz), was found to stimulate the production of tumor necrosis factor-α, interferon-gamma, interleukin-2, and interleukin-3 in healthy mouse cells and induce cytokine accumulation in blood plasma. Then, we studied the effect of this MF on tumor-bearing mice with solid tumors induced by Ehrlich ascite carcinoma cells by observing tumor development processes, including tumor size, mouse survival rate, and average lifespan. Tumor-bearing mice exposed to a combined constant magnetic field of 60 μT and an alternating magnetic field of 100 nT containing six frequencies showed a strong suppression of tumor growth with an increase in survival rate and enhancement of average lifespan.